FTIR Spectroscopic Study of Heat-Induced β-Lactoglobulin Solution under Flow Field - Sharma, R.K.; Furusawa, K.; Fukui, A.; Sasaki, N.; Masalova, I. (Asian Journal of Chemistry, 2018)
Effect of stirring on the secondary structure of amyloid fibrillogenesis of β-lactoglobulin (βLG) at pH 2 and at pH 7 with and without glucose was studied. Fibrillogenesis at pH 2 was carried out by heating the 4w % β-lactoglobulin and at pH 7 by heating the 0.30 mM β-lactoglobulin in 0.1 M, pH 7 sodium phosphate buffer solution with and without glucose (37.5 mM) for 24 h under stirring (250 and 474 rpm) conditions. For control samples, β-lactoglobulin solutions were incubated under unstirred condition at pH 2 and pH 7. The secondary structure of the amyloid fibrils which corresponds the β-sheet structure was studied by using Fourier transform infrared (FTIR) spectroscopy revealed that the stirring does not affect the secondary structure of the β-lactoglobulin fibrils at pH 2 as well as pH 7 with and without glucose.